HAEMATOLOGICAL AND BIOCHEMICAL ALTERATIONS OF CATLA CATLA FINGERLINGS FOLLOWING SUBLET EXPOSURE TO NUVAN - MEDDA, CHIRANJIB (Journal of Indian Fisheries Association, 2015)
The sublethal exposure (0.24 ppm) of Nuvan on some biochemical compositions such asserum protein, blood glucose, glutamate oxaloacetate transaminase (AST) and glutamatepyruvate transaminase (ALT) and on some haematological parameters such as red bloodcorpuscles (RBC), white blood corpuscles (WBC), haemoglobin content (Hb), mean corpuscularconcentration (MCV), mean corpuscular haemoglobin concentration (MCHC) of Calla callafingerlings were studied. The haematological and biochemical parameters evoked a significantreduction (excepting MCV, ALT and AST which is significantly increased) with increasing daysof Nuvan exposure